2017
DOI: 10.1590/1980-5918.030.003.ao01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pain, functional capacity, muscular strength and balance in young women with Patellofemoral Pain Syndrome

Abstract: Introduction: Patellofemoral Pain Syndrome (PFPS) is associated with anterior knee pain, changes in functional capacity, balance and muscle strength disorders. Objective: To quantify pain, functional capacity, strength in quadriceps (Q), gluteus medium (GM), hip external rotator (ER) muscles and balance in sedentary women with PFPS. Methods: Twenty sedentary women, aged 18 to 25 years, were divided into two groups: PFPS (N=10) and control group (N=10). All the volunteers answered the items of the Visual Analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
2
5
1
2
Order By: Relevance
“…Subgroup and meta-regression analyses did not indicate potential sources of heterogeneity (Additional file 7 ). Overall postural stability (15 studies [ 24 , 26 , 27 , 57 , 86 90 , 92 , 95 , 98 , 99 , 101 , 102 ] ): Moderate level evidence indicated that there is no difference between people with and without PFP for overall balance (SMD 0.38, 95% CI − 0.05–0.82; Fig. 4 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subgroup and meta-regression analyses did not indicate potential sources of heterogeneity (Additional file 7 ). Overall postural stability (15 studies [ 24 , 26 , 27 , 57 , 86 90 , 92 , 95 , 98 , 99 , 101 , 102 ] ): Moderate level evidence indicated that there is no difference between people with and without PFP for overall balance (SMD 0.38, 95% CI − 0.05–0.82; Fig. 4 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-regression indicated that age is not a source of heterogeneity (Additional file 7 ). Posteromedial (PM) postural stability (4 studies [ 85 , 95 , 96 , 98 ] ): Moderate level evidence indicated a very large and non-significant effect for lower reach during SEBT PM in people with PFP (SMD 1.22, 95% CI − 0.59–3.02; Fig. 5 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A incidência nos Estados Unidos está entre 3% e 6%, a característica principal do PFPS é a dor na região anterior do joelho, que se intensifica quando o joelho é flexionado durante as atividades de levantamento de peso. A dor da PFPS, geralmente piora quando o indivíduo permanece sentado por período prolongado ou quando desce de escadas (Zamboti, et al, 2017).…”
Section: Síndrome Da Dor Patelofemoral (Pfps) Ou Dor Patelofemoral (Pfp)unclassified
“…O tratamento da PFPS inclui repouso, um curto uso de anti-inflamatórios não esteroidais e fisioterapia direcionada ao fortalecimento dos músculos flexores do quadril e joelho. A bandagem patelar kinesio pode fornecer alívio adicional da dor de curto prazo; entretanto, as evidências são insuficientes para apoiar seu uso rotineiro (Zamboti, et al, 2017).…”
Section: Síndrome Da Dor Patelofemoral (Pfps) Ou Dor Patelofemoral (Pfp)unclassified